Masa Depan Penegakan Hukum Indonesia: Sistem Peradilan Pidana Berbasis Kecerdasan Buatan (AI) - Linda Ikawati; Sulaiman Sulaiman; Muhammad Fahri Huseini (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The era of technological disruption has brought about significant changes across various sectors, including the legal sector. One of the most prominent developments is the use of artificial intelligence (AI) in the judicial system. AI can be utilized for a wide range of tasks, from analyzing legal documents to predicting case outcomes, and even acting as a legal assistant. This study employed a qualitative approach by analyzing various sources such as journals, documents, and relevant research findings. The results of the study indicate that while AI offers numerous benefits, its application in the judiciary also faces several challenges. One of the primary challenges is the issue of data bias. The performance of AI heavily relies on the quality of the data used to train it. If the data contains biases, the resulting AI will also be biased. Additionally, concerns about privacy and data security are significant issues that need to be addressed.